115k views
1 vote
Solve the system y=x+5y=-3x+1The solution is (__,__)

User Rzaaeeff
by
5.0k points

1 Answer

5 votes

Step-by-step explanation:

-We must first use a method to match one of the variables, in this case for the variable y;

-After obtaining the value for the variable x, we must use the substitution method to find the value of the variable y.

The exercise is as follows:


\begin{gathered} y=x+5\text{ ; y }=-3x+1 \\ y=y \\ (x+5)=(-3x+1) \\ x+3x=1-5 \\ 4x=-4 \\ x=(-4)/(4) \\ x=-1 \\ \text{Now we must }substitute\text{ the value of x }in\text{ the equations;} \\ y=x+5 \\ y=(-1)+5 \\ y=4 \\ Now\text{ for: y}=-3x+1 \\ y=-3(-1)+1 \\ y=4 \\ \text{ANSWER: }(-1,\text{ 4)} \\ \end{gathered}

NOTE:

The exercise was correctly developed because it gave the same value for the variable y in both equations.

User Fahim Babar Patel
by
4.2k points